∈φ-contraction and some fixed point results via modified ω-distance mappings in the frame of complete quasi metric spaces and applications - Kamaleldin Abodayeh; T. Qawasmeh; W. Shatanawi; A. Tallafha (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this Article, we introduce the notion of an ∈φ-contraction which based on modified ω-distance mappings and employ this new definition to prove some fixed point result. Moreover, we introduced an interesting example and an application to highlight the importance of our work.